Pemberdayaan Usaha Mikro, Kecil, Dan Menengah (Umkm) Dengan Digital Marketing Di Desa Talang - Ahmad, Bisyrul Kafi Ibnu; Imaningsih, Niniek; Fadil, Cholid (Jurnal Ilmiah Wahana Pendidikan, 2023)
As the years go by, the technology in this world is also developing, the advancement of technology is a sign that in this day and age humans are required to be more developed in order to keep up with changing times, but sometimes some are still left behind due to several factors, such as lack of information or lack of information. interest in something more advanced, such as today's MSMEs, considering that before it was just a traditional market and became a modern market due to the impact of digitalization, with the creation of digital marketing, the marketing area has become wider, than previously it could only reach areas around, at this time it can almost reach all areas wherever MSMEs are located, we see that in Talang village there are still quite a lot of MSMEs that have not felt the impact of technological advances, of the several MSMEs in the village only 2 MSMEs are able to take advantage of digital marketing. This shows that MSMEs in Talang village still do not understand what digital marketing means. Some MSMEs may not have adequate knowledge about digital marketing or do not understand its potential and benefits. They may not know how to use digital platforms to promote and grow their business. Therefore, our goal in Talang village is to conduct outreach and assistance to increase the potential of MSMEs that have not yet developed in Talang village. From the results of our outreach and assistance in Talang village, it was noted that there were 4 MSMEs that were finally able to take advantage of digital marketing and there were also MSMEs that were still can't accept digital marketing yet.